Nilai Religius dalam Pembinaan Kader Perempuan Muslimat NU Kuwarasan - Pangestu, Dianah (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
Muslimat Nahdlatul Ulama (NU) is an organization that moves as a form of Nahdlatul Ulama's (NU) attention to women in order to gain religious values through Nahdlatul Ulama (NU). With the existence of the Muslimat Nahdlatul Ulama (NU) organization, Muslim mothers can spend their time with more positive things such as yasinan, tahlilan, recitation, and compensation for orphans, by participating in Muslimat Nahdlatul Ulama (NU) activities, it is hoped that in the future they can become women or Mulsimat mothers who fear Allah SWT earnestly, have good virtue, do charity, and can be responsible. The existence of the Muslimat Nahdlatul Ulama (NU) organization in Kuwarasan village is able to bring a change in the community, especially women, through yasinan activities, tahlilan, recitation, and compensation for orphans, with these activities Muslimat women must have undergone changes that used to rarely open or read yasin, now they are more diligent,